Insights into the design of an improved PfRH5 malaria immunogen using vaccine-induced monoclonal antibodies - Alanine, DGW (2017)
The causative agent of the most deadly form of malaria, P. falciparum, was identified over 130 years ago, yet this disease still causes 430,000 deaths each year. Although naturally-acquired immunity exists, it requires a heavy and sustained exposure to the parasite, with most succumbing as young children, before this immunity has fully developed. Effective treatments exist but with small-molecule drug resistance on the rise and little in the way of affordable alternatives, the need for an efficacious malaria vaccine is as great as ever. A successful malaria vaccine is likely to necessitate targeting each stage of the parasite's lifecycle. Immunity directed to the blood-stage, the stage which causes all the symptoms of malaria, is unique in that it would allow for a concomitant development of naturally-acquired immunity along with a reduction in morbidity and mortality. To date, antibody-mediated immunity to the blood stage requires intractably high levels of antibody and this problem is compounded by a paucity of viable candidates with which to effectively target different strains. Other fields of vaccinology, over the past decade, have been employing various structure-based strategies to increase the specific activity of the immune response thus lowering the antibody levels required for protection. However, very few detailed investigations of this kind have been conducted on a P. falciparum vaccine candidate, and certainly none as promising as PfRH5. In a world's first, fully-human antibodies raised in response to PfRH5 vaccination were isolated and extensively characterised, both functionally and structurally with the intention of elucidating the important features necessary to inform the design of an improved PfRH5-based vaccine. Synergistic and antagonistic effects of antibody combinations were noted and highlight new complexities of the immune response to PfRH5, opening the door to unanticipated potential for rational vaccine design.